2018
DOI: 10.1155/2018/6524629
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fuzzy Reliability Analysis of Multistate Systems Based on Universal Generating Function

Abstract: Considering the fuzziness of load, strength, operational states, and state probability, reliability models of multistate systems are developed based on universal generating function (UGF). The fuzzy UGF of load and the fuzzy UGF of strength are proposed in this paper, which are used to derive the fuzzy component UGF and the fuzzy system UGF. By defining the decomposition operator and the inner product operator, failure dependence and effects of multiple load applications are taken into account in the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Step 5: Establish improved FMSS availability index Given a target power demand of 3 1.9, 2.1, 2. ( ) 1 3 0 w    kW, the lower and upper bounds of the improved FMSS availability in the α-cut level set for the community-based smart grid can be obtained using the proposed constrained nonlinear parameter-planning model equations (14) and (15). As observed in this case study, the performances of states 3 and 4 overlap with the target power demand, i.e., ( Table 3 compares the results obtained in this study against those obtained using the method reported in [11].…”
Section: Step 3: Establish Fmsc Fugf and Fmss Ispmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 5: Establish improved FMSS availability index Given a target power demand of 3 1.9, 2.1, 2. ( ) 1 3 0 w    kW, the lower and upper bounds of the improved FMSS availability in the α-cut level set for the community-based smart grid can be obtained using the proposed constrained nonlinear parameter-planning model equations (14) and (15). As observed in this case study, the performances of states 3 and 4 overlap with the target power demand, i.e., ( Table 3 compares the results obtained in this study against those obtained using the method reported in [11].…”
Section: Step 3: Establish Fmsc Fugf and Fmss Ispmentioning
confidence: 99%
“…The effectiveness of their model was verified using a system in its design stage. Gao et al [15] considered the system workload and degradation intensity of components to establish their FMSS reliability model. Considering an MSS with multiple uncertain signals, Dong et al [16] introduced the standard interval fuzzy theory to expand the FUGF applicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional UGF method, however, only solves scenarios where the state performance of a component as well as the corresponding probability are real values and the relationships between components are dependent. To calculate the reliability of the system with fuzzy values, the fuzzy UGF method is presented to extend the traditional UGF with crisp sets 15,16 . Based on the fuzzy UGF method, Dong et al 17 analyze a generalized standard uncertain number to uniformly represent multisource heterogeneous uncertain data and Qiu et al 18 evaluate the fuzzy reliability of series systems with performance sharing between adjacent units.…”
Section: Introductionmentioning
confidence: 99%
“…27 Based on the assumptions that the applied loads used in the model were static and the hazard rates of mechanical systems were treated as the constants, Czarnecki, 28 Rackwitz, 29 Torres, 30 et al carried out the studies around the timevariant models for reliability analysis of various kinds of mechanical systems. To fully consider the dependence of hazard rates on strengths of components and applied loads, Wang, 31 Gao, 32 Castaldo, 33 Xie, 34 et al proposed various kinds of dynamic reliability models for mechanical systems by using probability differential equation and order statistics.…”
Section: Introductionmentioning
confidence: 99%